How to understand organizations under J. Etkin perspective - Korstanje, Maximilano (Nómadas. Critical Journal of Social and Juridical Sciences, 2009)
Double Moral in Organizations is a book that comprises concrete suggestions that allow us to understand critically the reasons as to why organizations -that take different formsmisunderstand their vision and mission according to institutionalized corruption. This point appears to be once and once again throughout this interesting book and will be criticized in the following review.